The role of surgery in the treatment of oligoprogression after systemic treatment for advanced non-small cell lung cancer. (November 2021) - Joosten, P.J.M.; de Langen, A.J.; van der Noort, V.; Monkhorst, K.; Klomp, H.M.; Veenhof, A.A.F.A.; Dickhoff, C.; Smit, E.F.; Hartemink, K.J.
Highlights: Resection of an oligoprogressive lesion after systemic therapy is feasible. Oligoprogressive surgery might be considered to achieve long term survival. M1 disease at initial presentation was predictive for better PFS. Clinical T4 stage was predictive for PFS. Superior PFS was seen after resection of the primary lung tumour. Abstract: Objectives: Patients with advanced stage non-small cell lung cancer (NSCLC) are generally considered incurable. The mainstay of treatment for these patients is systemic therapy. The addition of local treatment, including surgery, remains controversial. Oligoprogression is defined as advanced stage NSCLC with limited progression of disease after a period of prolonged disease stabilisation or after a partial or complete response on systemic therapy. In this retrospective study we evaluated outcome and survival of patients who underwent a resection for oligoprogression after systemic therapy for advanced stage NSCLC. Materials and Methods: Patients with oligoprogression after systemic treatment for advanced NSCLC who were operated in the Antoni van Leeuwenhoek Hospital were included. Patient and treatment characteristics were collected in relation to progression free survival (PFS) and overall survival (OS). Results: Between January 2015 and December 2019, 28 patients underwent surgery for an oligoprogressive lesion (primary tumor lung (n = 12), other metastatic site (n = 16)). Median age at time of resection was 60 years (39–86) and 57% were female. Postoperative complications were observed in 2 patients (7%). Progression of disease after resection of the oligoprogressive site was observed in 17 patients (61%). Median PFS was 7 months since date of resection (95% CI 6.0–25.0) and median OS was not reached. Seven patients (25%) died during follow-up. Age was predictive for OS and clinical T4 stage was predictive for PFS. M1 disease at initial presentation was predictive for better PFS compared to patients who were diagnosed with M0 disease initially. Patients who underwent resection because of oligoprogression of the primary lung tumour had a better PFS, when compared to oligoprogression of another metastastic site. Conclusion: Surgical resection of an oligoprogressive lesion in patients with advanced NSCLC treated with systemic treatment is feasible and might be considered in order to achieve long term survival.